LEVANTAMENTO DE QUESTÕES SOBRE A FALA DA CRIANÇA COMO OBJETO DE ESTUDO NO CAMPO DA AQUISIÇÃO DE LINGUAGEM - Carvalho, Glória (Intercâmbio, 2010)
This paper focus the following deadlock in the field of language acquisition: an effect caused by the child’s speech on the investigator constitutes that speech as the object of investigation, although such constitution suspends its objectivity statute. The referring deadlock could make the investigator come to resignifying his/her study object question.